2018 IEEE Global Communications Conference (GLOBECOM) 2018
DOI: 10.1109/glocom.2018.8647690
|View full text |Cite
|
Sign up to set email alerts
|

Low-Complexity and Robust Quantized Hybrid Beamforming and Channel Estimation

Abstract: Hybrid beamforming with phase shifters and switches has been identified as a low-cost and energy-efficient approach to harness the benefits of massive multiple-input multipleoutput (MIMO) systems. In this paper, three subconnected hybrid beamforming structures with different combinations of phase shifters and switches will be considered. Firstly we assume that perfect channel state information (CSI) is available and the wireless channel follows uncorrelated Rayleigh fading model. Then, we derive the closed-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It is noted that for L = 1, i.e. frequency-flat channel, our proposed RF beamformers becomes the same as narrow-and beamformer in [12], [31] and [21] turns into [5]. When L = 1, Fig.…”
Section: Simulation Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…It is noted that for L = 1, i.e. frequency-flat channel, our proposed RF beamformers becomes the same as narrow-and beamformer in [12], [31] and [21] turns into [5]. When L = 1, Fig.…”
Section: Simulation Resultsmentioning
confidence: 78%
“…When L = 1, Fig. 8 shows that using the RF beamformer of [5] results in a slightly higher spectral efficiency than [12], [31]; however, this is achieved at the cost of higher complexity.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For sparse channels, e.g., the THz channel in this work, the DoD and DoA are demanding information for hybrid beamforming design. While for rich scattering channels, it has been studied in [34] that the DoD and DoA can be mapped to the correlation matrix which is a realistic requirement for the hybrid beamforming design to achieve high spectral efficiency.…”
Section: A Channel Model and The Practical Partial Csimentioning
confidence: 99%
“…As a result, they have been identified as one of the most promising approaches to implement systems that are based on 802.11 ay and 5G new radio. Hybrid beamformers can be divided into subconnected and fullyconnected structures, as shown in Figure 1 [18]- [20]. Theoretical analysis of different structures has shown that fullyconnected hybrid beamformers provide significantly more degrees of freedom to design algorithms and reach higher data rates.…”
Section: Introductionmentioning
confidence: 99%